Respiratory distress in late-preterm neonates: from controversy to consensus – a survey of regional advisory boards and neonatologists in France - Elie Saliba; Delphine Mitanchez; Jean Michel Hascoet; Yoni Athea (BMJ Paediatrics Open)
Objective Late-preterm neonates present with more complications at birth than full-term neonates. The care of these infants is sometimes controversial. Our study aims at examining the practices of French neonatologists and compares them to the literature.Design Regional advisory boards discussed a clinical case with four categories of questions: the risk of term-related respiratory distress (RD), the indication for antenatal corticosteroid therapy, neonatal care at delivery and the use of surfactant. An anonymous survey covering the same question categories was also sent to French neonatology departments.Results For the risk of RD, the boards’ responses were somewhat unclear. Conversely, the survey highlighted the association between high risk of RD and low term of birth, which is in agreement with the literature. The boards noted that, in the absence of official recommendations, they would not advise using antenatal corticosteroids. However, the survey recommended their use in cases of threatened prematurity (32%). For neonatal care at delivery, the boards and survey recommended the standard use of continuous positive airway pressure (CPAP) as advised in the literature. Lastly, the boards and survey agreed that surfactant therapy is part of usual care. Published recommendations do not support its systematic use except when RD is present.Conclusion This study confirms that late-preterm infants have an often-underestimated vulnerability. Morbidity is inversely correlated with gestational age, and caution is required over the place of birth. Antenatal steroid treatment remains controversial. There is consensus over the use of CPAP at delivery and of surfactant as early curative therapy.